OPERACJE OTWARTEGO RYNKU W POLSCE W LATACH 1993-2002 - Przybylska-Kapuścińska, Wiesława (Wydział Prawa i Administracji UAM, 2003)
The paper presents Open Market Operations as the most popular and innovative monetary policy instrument used in market economy. On the one hand, the development of these operations and their intensive application in the Polish money market indicates the decreasing importance o f the administrative instruments in the state policy on market regulation o f money supply. On the other hand, the growing scale o f the Open Market Operations, as well as the changes in the type o f operations, point to the still existing problem o f overliquidity o f the banking system in Poland. The presence o f these phenomena indicates that some action has to be taken to reduce overliquidity.
OPEN MARKET OPERATIONS IN POLAND IN 1993-2002